Biobriquetting in Nepal - Scope and Potentials: A Review - Singh, Ramesh M. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Nepal still relies heavily on traditional sources of energy for cooking, heating, and livestock feeding. In search for alternatives to fuel wood and utilization of waste biomass, briquetting was introduced in 1982 by the private sector to produce charred rice briquettes and rice husk briquettes in 1987. A close analysis of the situation during the 1980s reveals that the entire briquetting efforts came from the private sector, without any government support in terms of policies, incentives, and motivation. Also, there was no technical backstopping and very little R&D to support briquetting. So because of various techno-economic problems, most of the briquetting industries closed down. The situation in the country after 2010, nearly thirty years later, is entirely different. With the increase in awareness about briquettes as a renewable source of energy, climate change, and global warming issues from fossil fuel use, and the concept of utilizing waste for energy, along with the change in kerosene and briquettes fuel prices, briquettes are slowly emerging as a viable alternative source of energy for cooking and heating. Many briquetting industries are again being established in the private sector. The Nepali experience on briquetting shows that almost all of the biobriquetting technologies have been introduced in the country. R&D institutions have emerged, and research and development activities supporting biomass briquetting are constantly increasing. The assessment of agro-forest waste shows that there is a huge raw material base that can be utilized for briquetting. The technological capability in fabrication, reproduction, repair, and maintenance has been well developed. Many funding, promotional, and R&D organizations are now actively involved in briquetting. The Government through the Alternative Energy Promotion Centre (AEPC) is formulating policies, plans, and programs, including incentives for the promotion of biobriquetting. With the introduction of proper policies and incentives, biomass briquetting has big potentials and scope for the promotion of biobriquettes in the near future.